(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The purpose of this study was to determine whether Physical activity could reduce violent behavior among undergraduate Sport Science students and may differ according to gender. The sample of study consisted of (80) male and female students of the expected graduating students in the Faculty at a rate of (%80) from the original community. a questionnaire consisted of (10) paragraphs was used. And after doing the suitable statistical treatments it was pin-pointed that practicing the sport activities has a big role in belittling the level of violence and at a very big degree amongst students of the Faculty of Physical Education and Sport Science in theHashemiteUniversity, and there are no differences between males and females. The researchers recommended with the necessity of preparing more studies about the phenomenon of violence for the different age stages.